2019
DOI: 10.33225/jbse/19.18.634
|View full text |Cite
|
Sign up to set email alerts
|

Using Board Games to Teach Socioscientific Issues on Biological Conservation and Economic Development in Taiwan

Abstract: This research uses board games as teaching material to develop students’ decision-making ability and basic scientific literacy and to foster students’ value for nature and social caring by working with socioscientific issues. The board game structure contains four perspective systems: ecological, economic, cultural, and political. In the game processing, students must handle, consider, and understand the different role players’ positions and face different missions that involve socioeconomic and environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…Furthermore, it provided an opportunity to train students to contemplate professional situations [2]. Moreover, this activity could strengthen participants' understanding of the relationships between various positions related to SSIs [23]. Students in previous studies also reported these effects.…”
Section: Issue Situations For Opinions On Forming Rolesmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, it provided an opportunity to train students to contemplate professional situations [2]. Moreover, this activity could strengthen participants' understanding of the relationships between various positions related to SSIs [23]. Students in previous studies also reported these effects.…”
Section: Issue Situations For Opinions On Forming Rolesmentioning
confidence: 94%
“…For solving methods to be effective and consistent, it is vital that the participants reach a consensus on them [1,22]. Therefore, in some situated learning cases, educators assigned students to different groups in which each student played a role in addressing a specific issue to teach them how to reach a consensus [16,23]. However, the different roles assigned can lead to differences in the students' learning outcomes.…”
Section: Role Playing In Learning and Its Possible Disadvantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 1 is to find out students' difficulties in learning chemical elements and the periodic table. Students often have low learning motivation because they do not know how chemical elements are relevant to their life experiences [15,16,18]. Therefore, in step 2, the researchers have reasons to decide which chemical elements and relevant information about their techniques and products should be selected for inclusion in the card game.…”
Section: Game Content and Rulesmentioning
confidence: 99%
“…Previous research suggested that science board games should simulate students to apply scientific knowledge when dealing with life situations. Moreover, if the only topic that was gamified was the scientific concept, for middle school students who have studied only the basic concepts of chemistry, it is difficult to maintain interest in playing the games [15][16][17]. Therefore, there is still room for improvement in the current scientific board games in teaching the periodic table of the chemical elements.…”
Section: Introductionmentioning
confidence: 99%